Exploring the Experiences of People With Hypo- and Hyperthyroidism. (July 2015) - Nexø, Mette A.; Watt, Torquil; Cleal, Bryan; Hegedüs, Laszlo; Bonnema, Steen J.; Rasmussen, Åse K.; Feldt-Rasmussen, Ulla; Bjorner, Jakob B.
Thyroid diseases evoke a complex range of psychological and physical symptoms. The psychosocial aspects of living with diseases causing hypo- or hyperthyroidism are poorly understood. In this article, we report the findings of a qualitative interview study in which we explored the lived experiences of 16 people with hypo- or hyperthyroidism. We purposefully selected participants from Danish outpatient clinics according to their diagnosis (Hashimoto's thyroiditis or Graves' disease with or without orbitopathy), age (18 to 65 years), and duration of treatment (more than 6 months). We used interpretative phenomenological analysis (IPA) as a theoretical frame and analytical approach and identified three superordinate themes: losing control over mental and physical states, ambiguous signs of disease, and negotiating sickness. We discuss the findings in the context of the recent literature on chronic illness and argue that these themes play an important role in the conceptualization and management of thyroid diseases.